Unveiling Identity - Ömer Gökhan Ulum (Names)
This study explores the pervasive impact of name bias on Kurdish-origin individuals and Syrian Arab refugees within Turkey's socio-political landscape. Using quantitative methodology, the research developed a Likert-scale questionnaire through exploratory factor analysis, identifying five key factors: Personal Experiences, Institutional Practices, Societal Perceptions, Personal Attitudes, and Occupational Settings. Grounded in social identity theory and Allport's contact hypothesis, the study investigates the influence of name bias on socioeconomic opportunities, cultural integration, and psychological well-being. The findings show significant disparities in perceived name bias across ethnicities, genders, and educational levels, with Kurdish-origin individuals experiencing higher bias in personal and institutional contexts. Further, this study highlights the intersectionality of name bias and its amplification by societal structures. It provides empirical insights from a non-Western context, advocating for systemic policy, education, and workplace changes to reduce name-based discrimination. Finally, this study contributes to the field of onomastics, emphasizing the need for targeted interventions to create an inclusive society where one's name does not constrain identity and opportunities.